A study of relationship office design and employees productivity in Micost / Nur Safirah Izati Ahmad - Ahmad, Nur Safirah Izati (Faculty of Business and Management, 2018)
Office design plays an important role for employees’ productivity. Unfortunately many organizations neglected the importance of evolving workspace into new environments that was more convenient to increase the employees’ productivity. Thus the purpose of this study was to know the level of employees’ productivity in the present population (MiCoST). Next, to prove whether there are any relationship between employees productivity or not and to know which factor most influencing to the employees’ productivity. All the analysis on the effect of office design towards employee productivity will present in this study. The research focused on four variables furniture, noise, lighting and spatial arrangement and investigate its relationship towards employee productivity. In this study, there are 144 population and 103 sample size of employees’.120 sets of questionnaire had been distributed among the employees using convenient sampling method. Findings of this research shows that, the level of employee productivity were high. All four variable, noise, lighting, furniture and spatial arrangement have high mean score as well. Next, the correlations analysis, highlights all the factors of office are significant, strong and positive correlation with employee’s productivity. Next, R square for this study was 0.584 showed that independent variable in this study only give 58.4%. While, for the most influencing factors in this study were, spatial arrangement which had the highest value of beta coefficient. (0.423). To conclude, it showed that, office design plays an important roles to ease employees daily task and boost their productivity.